2015
DOI: 10.1097/wnq.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

Double-loculated Calcification Chronic Subdural Hematoma

Abstract: Calcified chronic subdural hematoma (CCSDH) is a rare pathologic entity and, until recently, has been only published as case reports. We first present a patient with a doubleloculated CCSDH who obtained good reexpansion after craniotomy to remove the thick calcified inner membrane and hematoma. In addition, we reviewed 46 cases in literature and conducted a summary about the incidence, clinical characteristics, radiologic findings, and therapeutic strategies of CCSDH. Surgical treatment for CCDSH with a sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…A CT scan performed after this second operation showed that the volume of the hematoma had decreased and that the calcified cavity was communicating with the subdural space beneath (►Fig. 3).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…A CT scan performed after this second operation showed that the volume of the hematoma had decreased and that the calcified cavity was communicating with the subdural space beneath (►Fig. 3).…”
Section: Case Reportmentioning
confidence: 99%
“…1 Its overall yearly incidence ranges from 1.72 to 20.6 per 100 thousand persons. 2 Between 0.5% and 2.0% of the cases of CSDH 3 undergo calcification, and they are known as calcified DSDHs (CCSDHs); their first known description was made by von Rokytansky in 1884. 4 Due to its similarity with an armor encapsulating the brain, this entity is sometimes referred to as armored brain .…”
Section: Introductionmentioning
confidence: 99%